Conceptualizing citizen participation in open data use at the city level. Issue 1 (20th March 2017) - Hivon, Julien; Titah, Ryad
Abstract : Purpose: Open data initiatives represent a critical pillar of smart cities' strategies but remain insufficiently and poorly understood. This paper aims to advance a conceptualization of citizen participation and investigates its effect on open data use at the municipal level. Design/methodology/approach: Based on 14 semi-structured interviews with citizens involved in open data projects within the city of Montréal (Canada), the paper develops a research model linking the multidimensional construct of citizen participation with initial use of open data in municipalities. Findings: The study shows that citizen participation is a key contributor to the use of open data through four distinct categories of participation, namely, hands-on activities, greater responsibility, better communication and improved relations between citizens and the open data portal development team. While electronic government research often views open data implementation as a top-down project, the current study demonstrates that citizens are central to the success of open data initiatives and shows how their role can be effectively leveraged across various dimensions of participation. Originality/value: This paper proposes a conceptualization of citizen participation on open data use at the municipal level. Citizen participation is a found to be a key contributor to the use of open data through four distinct categories of participation, namely, hands-on activities, greater responsibility, better communication and improved relations between citizens and the open data portal development team. This paper demonstrates the critical role of citizen participation in open government.